2023
DOI: 10.3390/jcm12134274
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Evidence of Multiple Sclerosis Diagnosis and Treatment Challenges

Abstract: Multiple sclerosis (MS) is a chronic autoimmune disease that impacts the central nervous system and can result in disability. Although the prevalence of MS has increased in India, diagnosis and treatment continue to be difficult due to several factors. The present study examines the difficulties in detecting and treating multiple sclerosis in India. A lack of MS knowledge among healthcare professionals and the general public, which delays diagnosis and treatment, is one of the significant issues. Inadequate nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 274 publications
0
9
0
Order By: Relevance
“…As a result, disease symptoms worsen, and the myelin sheath rapidly degrades and is engulfed by macrophages, increasing the demyelinating area [100,101]. Numerous investigations have demonstrated that MeHg+ demyelinates nerve cells in a mouse model of ALS [39].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, disease symptoms worsen, and the myelin sheath rapidly degrades and is engulfed by macrophages, increasing the demyelinating area [100,101]. Numerous investigations have demonstrated that MeHg+ demyelinates nerve cells in a mouse model of ALS [39].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal fluctuations, decreased physical activity, and alterations in body composition cause age-related fluctuations in the metabolism of individuals. These metabolic alterations may all impact dietary absorption, energy expenditure, and metabolic rate [ 96 ]. Age-related metabolic changes have been linked to a higher incidence of cardiovascular disease, metabolic syndrome, and insulin resistance in the elderly [ 97 ].…”
Section: Exercising Caution In Ppi Prescriptions: Addressing the Pote...mentioning
confidence: 99%
“…Timely diagnosis of MS enables effective therapy and minimizes unpredictable dysfunction [ 3 ]. Efforts have been made to improve diagnostic criteria for MS recently [ 4 ]. The latest standard for MS diagnosis comprises clinical symptoms, magnetic resonance imaging lesions, cerebrospinal fluid (CSF) specific oligoclonal bands and exclusion of other diagnostic possibilities [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many other markers are impacted by treatment effects or lack specificity. Although developing reliable biomarkers remains challenging, continuing studies are making effort to address the unmet need for an accessible and accurate diagnostic approach for MS [ 3 , 4 ]. Notwithstanding specific triggers are still unexplicit, epidemiologic studies have considered that genetically predisposed individuals may develop MS for some certain environmental factors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%